Level Of Knowledge Self-Medication Of Dysmenorrhea, Iron Supplement Consumption During Menstruation Student SMK Kesehatan Banten - Dewantoro, Agung; Ismaya, Nurwulan Adi; Rahajeng, Sunny Koswara; Anggraeni, Niken Diah; Nurlela, Nurlela (Journal of Pharmacy and Nutrition Research, 2025)
Dysmenorrhea has an impact on young women, it can causing disturbances in daily activities. Losing blood during menstruation can affect iron lever in the body. women who menstruate monthly having risk of anemia. The prevalence of primary dysmenorrhea is 54.89% and the prevalence of anemia in Indonesia is 19.7% in women. Dysmenorrhea is often considered normal even though it affects daily activities so that adolescents do not visit health facilities but do self-medication. The purpose of riset is to find out the level of self-medication knowledge of dysmenorrhea drugs and the consumption of iron supplements during menstruation in students of the Banten Health Vocational School. The research method uses a descriptive design with a quantitative approach. Data was collected using a questionnaire that was distributed to 138 respondents who were selected using accidental. Results The level of self-medication knowledge of dysmenorrhea drugs was 65 repsondens or 40.10% in the good category, the level of knowledge of iron tablet consumption during menstruation was 66 respondents or 47.83% in the fair category. The conclusion of this study is that most of the students have an understanding and knowledge of self-medication dysmenorrhea and the consumption of iron tablets during menstruation.